2021
DOI: 10.3389/fimmu.2021.737170
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral-Cardiac Syndrome and Diabetes: Cardiac Damage After Ischemic Stroke in Diabetic State

Abstract: Cerebral-cardiac syndrome (CCS) refers to cardiac dysfunction following varying brain injuries. Ischemic stroke is strongly evidenced to induce CCS characterizing as arrhythmia, myocardial damage, and heart failure. CCS is attributed to be the second leading cause of death in the post-stroke stage; however, the responsible mechanisms are obscure. Studies indicated the possible mechanisms including insular cortex injury, autonomic imbalance, catecholamine surge, immune response, and systemic inflammation. Of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 118 publications
0
17
0
1
Order By: Relevance
“…Some research statistics show that the number of diabetic patients in the world is as high as 25.6% in 2015 [ 3 ]. DM is easy to cause various complications, and stroke is a common complication of DM [ 4 ]. According to relevant studies, the relative risk of stroke patients with DM is 1.8-6.0, and the combined disability rate and mortality rate are higher [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some research statistics show that the number of diabetic patients in the world is as high as 25.6% in 2015 [ 3 ]. DM is easy to cause various complications, and stroke is a common complication of DM [ 4 ]. According to relevant studies, the relative risk of stroke patients with DM is 1.8-6.0, and the combined disability rate and mortality rate are higher [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, T2DM cannot be cured and requires long-term drug control, but prolonged disease is likely to cause multisystem damage, leading to chronic progressive lesions and hypofunction of multiple organs, threatening the life and health of patients [ 3 ]. Cerebral stroke (CS) is a common complication of T2DM, caused by obstruction of blood circulation in the brain; its morbidity and mortality rates are much higher than those of other brain injury diseases, and the disability rate is increasing [ 4 , 5 ]. Therefore, facing patients with T2DM combined with CS requires not only effective pharmacological control but also improving patient self-management, safeguarding patients' recovery process, and promoting a positive mindset are crucial for disease treatment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our prior work, as well as others have demonstrated that stroke in non-DM and T2DM mice induces significant and progressive cardiac dysfunction compared to corresponding control mice ( Yan et al, 2020 ; Chen et al, 2021 ). T2DM aggravates such cerebral-cardiac syndrome ( Lin et al, 2021 ; Venkat et al, 2021 ). Acute ischemic stroke patients who developed acute kidney injury had higher risk of mortality at 3 months after stroke ( Qureshi et al, 2020 ; Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%